New insights into the anti-erosive property of a sugarcane-derived cystatin: different vehicle of application and potential mechanism of action - Gironda, Carlos Condarco; Pelá, Vinícius Taioqui; Henrique-Silva, Flávio; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP]; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2022)
OBJECTIVE: A new sugarcane-derived cystatin (CaneCPI-5) showed anti-erosive properties when included in solutions and strong binding force to enamel, but the performance of this protein when added to gel formulations and its effect on surface free energy (SFE) requires further studies. 1) to evaluate the protective effect of gels containing different concentrations of CaneCPI-5 against initial enamel erosion (Experiment 1); and 2) to analyze the SFE (γS) after treating the enamel surface with CaneCPI-5 solution (Experiment 2). METHODOLOGY: In Experiment 1, 75 bovine enamel specimens were divided into five groups according to the gel treatments: placebo (negative control); 0.27%mucin+0.5%casein (positive control); 0.1 mg/mL CaneCPI-5; 1.0 mg/mL CaneCPI-5; or 2.0 mg/mL CaneCPI-5. Specimens were treated with the gels for 1 min, the AP was formed (human saliva) for 2 h and the specimens were incubated in 0.65% citric acid (pH=3.4) for 1 min. The percentage of surface hardness change (%SHC) was estimated. In Experiment 2, measurements were performed by an automatic goniometer using three probing liquids: diiodomethane, water and ethylene glycol. Specimens (n=10/group) remained untreated (control) or were treated with solution containing 0.1 mg/mL CaneCPI-5, air-dried for 45 min, and 0.5 µL of each liquid was dispensed on the surface to measure contact angles. RESULTS: Gels containing 0.1 and 1.0 mg/mL CaneCPI-5 significantly reduced %SHC compared to the other treatments (p<0.05). Treated enamel showed significantly lower γS than control, without changes in the apolar component (γSLW), but the polar component (γSAB=Lewis acid-base) became more negative (p<0.01). Moreover, CaneCPI-5 treatment showed higher γS - (electron-donor) values compared to control (p<0.01). CONCLUSIONS: Gels containing 0.1 mg/mL or 1.0 mg/mL CaneCPI-5 protected enamel against initial dental erosion. CaneCPI-5 increased the number of electron donor sites on the enamel surface, which may affect AP formation and could be a potential mechanism of action to protect from erosion.